The role of work-home interference and workplace learning in the energy-depletion process - Joris van Ruysseveldt; Karin Proost; Peter Verboon (Management Revue, 2011)
In this study, we tested a work stress model which incorporates both an energydepletion and a workplace learning process. In the energy-depletion process, workhome interference was assumed to mediate the relationship between job demands (workload, emotional demands) and psychological fatigue. In the workplace learning process it was hypothesized that workplace learning mediated the relationship between job resources (autonomy, task variety) and psychological fatigue. Results of a multi-group structural equation modelling (N = 9738) confirmed our hypotheses and as such contribute to a better understanding of the interplay between job characteristics and stress-related outcomes.
Keywords: J24; J81; 650; learning opportunities; psychological fatigue; work-home interference; Job Demands-Resources model